Why Street-Level Bureaucrats Leave: The Effects of Organizational Transparency and Role Conflict - Tingzhong Huang; Wenyan Tu (The American Review of Public Administration, 2026)
Street-level bureaucrats often lack workplace clarity, which contributes to higher turnover. Drawing on street-level bureaucracy theory and the Job Demands–Resources model, this study examines how organizational transparency and role conflict, two dimensions of workplace clarity, shape turnover intentions among social workers in Chinese nonprofit organizations. Using multilevel data from the China Social Work Longitudinal Study, we find that organizational transparency reduces and role conflict increases turnover intentions. Value fit mediates both relationships, and job autonomy moderates them by enhancing the benefits of organizational transparency and buffering the harms of role conflict. Findings validate the extension of street-level bureaucracy theory to the nonprofit context and offer actionable insights for improving workforce stability in a complex governance environment.